Toxoplasma gondii infection among pregnant women in Yemen: Factors associated with high seroprevalence - Al-Eryani, Samira M.; Al-Mekhlafi, Abdulsalam M.; Al-Shibani, Latifa A.; Mahdy, Mohammed M. K.; Azazy, Ahmed A. (JIDC Central Office, 2016)
Introduction: Although toxoplasmosis is an important public health problem, there is scarcity of data on the disease available from Yemen. A cross-sectional survey was conducted in health facilities to determine seroprevalence of Toxoplasma gondii and associated risk factors among pregnant women in Sanaa, the capital city of Yemen. Methodology: A total of 593 pregnant women were included and examined for anti-T. gondii antibodies (Ab) using enzyme-linked immunosorbent assay. Bio and socio-demographic data were collected by pre-tested structured questionnaires through face-to-face interviews. Results: The overall seroprevalence of T. gondii was 45.4% (95% confidence interval: 41%-49%). The prevalence of anti-T. gondii IgG and IgM was 43.7 (95% CI: 40-%48%) and 9.1% (95% CI: 7%-12%), respectively. About 7.4 (95% CI: 6%-10%) of pregnant women were seropositive for both IgG and IgM Abs. Multivariate logistic regression analysis identified the following risk factors for toxplasmosis (IgG and/or IgM): age ? 25 years (adjusted OR: 2.02, 95% CI: 1.44-2.84, p < 0.001), rearing cats in the house (OR: 1.75, 95% CI: 1.20-2.55, p = 0.004), and contact with soil (OR: 1.90, 95% CI: 1.32-2.75, p = 0.001). Conclusions: The study reported high seroprevalence among pregnant women in Sanaa, Yemen, with a high proportion of pregnant women having a possibility of acute toxoplasmosis. This highlights the need for including routine screening for T. gondii in pregnant women in the countrys antenatal clinics. In addition, health education on the mode of transmission of toxoplasmosis should be provided for pregnant women in Yemen.